Brazil’s 2014 presidential elections: the interconnection between election news and stock market behavior - Werth, Luca Camilla (2016)
This study researches whether there has been abnormal stock market behaviour in Brazil as a consequence of election news (observed via opinion polls), regarding the last Brazilian presidential election, held in October 2014. Via applying event study methodology, the research on the Ibovespa and Petrobras suggests that events in which Rousseff was gaining in share have been subject to negative abnormal returns, and events where Rousseff was loosing in share have led to positive abnormal returns. Moreover, volatility has been significantly elevated during the election period and volume has been found to have slightly increased.